PENILAIAN KINERJA 360 DERAJAT SEBAGAI USAHA MENINGKATKAN PERSEPSI POSITIF TERHADAP KEADILAN PROCEDURAL PENILAIAN KINERJA - Widyowati, Arini (Universitas Ahmad Dahlan, 2010)
Performance appraisal is a crucial aspect to effective human resource management. However there are evidences that current processes are not very effective. Employees will accept the appraisal system if they perceive that the procedure on appraisal system is fair. This study reports the experience with relatively new appraisal system. The system of 360 degree performance appraisal, utilizes ratings from peers, supervisor, and employee. This experiment used 26 of college students from one of university in Yogyakarta as subjects that were divided randomly in to experiment group and control group. Perceive of procedural fairness scale was used to measure perceive of performance appraisal procedural fairness. Result supported the hypotheses that 360 degree performance appraisal was effective to increase perceive of performance appraisal procedural fairness (F=89.229; p= 0.000; p<0.05) and gave 78.8 % to perceive of performance appraisal procedural fairness. The result also indicated that there was a significant difference between experiment group and control group after the intervention was given to experiment group (F=18.416; p=0.000 p>0.05). Perceive of performance appraisal procedural fairness on experiment group significantly increased after 360 degree performance appraisal simulation was given (F=91.460; p=0.000; p<0.05).